2013
DOI: 10.1007/s12094-012-0987-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for acute toxicity in prostate cancer patients treated with high-dose hypofractionated radiotherapy

Abstract: This 5-week dose-escalation hypofractionated radiotherapy schedule that uses 3D-conformal radiotherapy without IGRT has resulted in <1 % grade 3 acute complications. Our study suggests that reducing the mean rectal dose and the bladder V 65 helps prevent acute toxicity. TURP before radiotherapy was associated with lower acute GU toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Indeed, our results demonstrate that overall acute rectal morbidity is near its maximum several days after the completion of SBRT, improves by 1 month, and returns to baseline by approximately 3 months. Here, we report that 23% of patients experienced ≥ grade 2 acute GI toxicity at 1 week, an incidence which is comparable to those reported for conventional fractionated radiation therapy ( 9 , 10 ). However, even mild bowel toxicity can adversely affect quality of life ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, our results demonstrate that overall acute rectal morbidity is near its maximum several days after the completion of SBRT, improves by 1 month, and returns to baseline by approximately 3 months. Here, we report that 23% of patients experienced ≥ grade 2 acute GI toxicity at 1 week, an incidence which is comparable to those reported for conventional fractionated radiation therapy ( 9 , 10 ). However, even mild bowel toxicity can adversely affect quality of life ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…In comparison, patients in the control arm, which used conventionally fractionated rt, experienced toxicity peaking at weeks 7-8 20 . In another prospective study 18 that delivered 70.2 Gy in 27 fractions, the highest degree of acute toxicity occurred at 4-5 weeks. Grade 2 or greater gu toxicity was found in 32.6% of patients, and grade 2 or greater gi toxicity was seen in 10% of patients.…”
Section: Discussionmentioning
confidence: 95%
“…For acute gu toxicity (specifically of the bladder), the V 65 18 and V 50 8 have been reported to be statistically significant. In addition, in multivariate analysis, Macias et al 18 illustrated that the bladder volume receiving 65 Gy or more (V 65 ) is associated with an increased risk of gu complications (p = 0.017), and that the mean rectal dose and total dose are significantly related to gi toxicity ( p = 0.013 and p = 0.019 respectively). Future analysis of data from phase i/ii studies will provide dose-volume histogram safety parameters for hfrt, with ranges of dose and fractionation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed a very low risk of severe toxicity without any grade >3 side effects, even including PC patients treated after surgery or using hypofractionated RT. In this respect, Macias et al (29) had already observed <1% grade 3 acute complications in PC patients treated with a hypofractionated schedule.…”
Section: Discussionmentioning
confidence: 93%